THE „OHRID SUMMER FESTIVAL“ ̶ AN OPEN STAGE FOR INTERCULTURAL DIALOGUE BETWEEN THE SLAVIC PEOPLES (Philological Studies, 2025)
The purpose of the paper is to present the „Ohrid Summer Festival“ and its role in creating conditions for deepening the intercultural dialogue between the Slavic peoples in the first decade of the 21st century. Through the methods of historical, analytical and descriptive research, we inquire into how a dialogue develops on stage between artistic disciplines, as well as between national and internationally established artists  ̶ representatives of Slavic cultures. They appear as performers of chamber and symphonic works, but also as soloists (instrumental musicians) interpreting larger or smaller musical forms of high artistic value.
Keywords: „Ohrid Summer Festival“, Program Contents, Slavic Peoples, Musical-Stages Works, Classical Music, Intercultural Dialogue